STUDI ANALISIS UPAYA MANAJER DALAM REALISASI PERENCANAAN STRATEGIS RSUD KABUPATEN EMPAT LAWANG MELALUI PENDEKATAN BALANCED SCORECARD (BSC) - yesica tria enggriani; Hanny Handiyani; Rr. Tutik Sri Hariyati; Dumilah Ayuningtyas (Indonesian Journal of Nursing Scientific, 2024)
An Analytical Study Of Managers' Efforts In The Realisation Of Strategic Planning Of RSUD Kabupaten Empat Lawang Through The Balanced Scorecard Approach. Although strategic planning has been prepared in such a way as to choose the best approach, in practice, many managers have difficulty realising the plan. This study aims to analyse the steps and efforts in realising strategic planning at RSUD Empat Lawang Regency through the BSC approach. The method used is a case study through SWOT analysis (Strength, Weakness, Opportunity, and Threat). Data were obtained through a document review of the hospital's profile and achievements. The data were then analysed for external and internal situations using the SWOT method, then inputted into the Internal Factor Evaluation (IFE) matrix and External Factor Evaluation (EFE) matrix to be given weight and scale, and determined the position of the organisation through the Internal-External (IE) matrix. Then strategies were formulated through Threat, Opportunity, Weakness, and Strength (TOWS) followed by the determination of Balanced Scorecard (BSC) perspectives and Key Performance Indicators (KPIs). The results of the analysis show that the RSUD is in cell IV, which means that the RSUD is best controlled with a growth and build strategy so that 10 targets are obtained along with the manager's efforts in realisation which include measuring Value For Money, collaborating with other parties, developing innovations and preparing education and training plans. The managers' efforts in this study can be used as a reference in evaluating the realisation of strategic plans in health service organisations.